Report of the International Narcotics Control Board for 2015 - United Nations Office on Drugs and Crime (New York : United Nations, 2016)
This annual report prepared by The Board provides a comprehensive account of the global drug situation, analyses trends in drug abuse and drug trafficking and suggests necessary remedial action. Divided into four parts, it covers the following topics: drugs and corruption, functioning of the international drug control system, analysis of the world situation and finally, a set of recommendations to Governments, the United Nations and other relevant international and regional organizations. A set of Annexes follows as well.
Keywords: Substance-Related Disorders -- prevention and control; Drug Trafficking -- prevention and control; Drug Addiction; Drug Dependence